Pengaruh Penggunaan Multimedia Interaktif Power Point Terhadap Minat Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam - Sodikin, Ahmad; Surami, Surami (JUPIN (Jurnal Pendidikan Islam Nusantara), 2023)
This study aims to determine the influence of PowerPoint media on students' learning interest in the subject of Islamic Education. This objective is motivated by the low learning interest of students in studying Islamic Education. The research employs a quantitative method by conducting an experiment to examine the impact of using PowerPoint media on students' learning interest during the classroom learning process. Regression analysis using SPSS version 16 is employed to analyze the data. The findings of this research are as follows: 1) There is a significant difference in students' learning interest before and after using PowerPoint media at SMP Negeri 02 Madang Suku II, as evidenced by the average pre-test score of 66.2903 and the average post-test score of 71.0323. 2) There is an influence of using PowerPoint media on students' learning interest in the subject, with an effect size of 32%, a significance value of 0.001, and an R-square value of 0.322.